2020
DOI: 10.1038/s41380-020-00914-0
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate relationships between peripheral inflammatory marker subtypes and cognitive and brain structural measures in psychosis

Abstract: Elevations in peripheral inflammatory markers have been reported in patients with psychosis. Whether this represents an inflammatory process defined by individual or subgroups of markers is unclear. Further, relationships between peripheral inflammatory marker elevations and brain structure, cognition, and clinical features of psychosis remain unclear. We hypothesized that a pattern of plasma inflammatory markers, and an inflammatory subtype established from this pattern, would be elevated across the psychosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
67
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(80 citation statements)
references
References 81 publications
10
67
3
Order By: Relevance
“…using composite scores analyses [44], regularized regression [45], k-means clustering [26,46,47], or through a combination of unsupervised exploratory factor analysis and hierarchical clustering [48]. Consistent with our findings, the majority of these previous studies demonstrated that inflammatory profiles in patients with psychotic disorders can be sub-grouped into two main clusters, namely "high inflammatory" and a "low inflammatory" subgroups.…”
Section: Discussionsupporting
confidence: 90%
“…using composite scores analyses [44], regularized regression [45], k-means clustering [26,46,47], or through a combination of unsupervised exploratory factor analysis and hierarchical clustering [48]. Consistent with our findings, the majority of these previous studies demonstrated that inflammatory profiles in patients with psychotic disorders can be sub-grouped into two main clusters, namely "high inflammatory" and a "low inflammatory" subgroups.…”
Section: Discussionsupporting
confidence: 90%
“…2f and g). Similar to existing clinical studies 7,[15][16][17]30,31 , our results demonstrate there is a BBB-deficit subgroup in psychotic disorders characterized by more extensive BBB disruption as evidenced by decreased TEER, increased permeability, lower CLDN5 intensity, and aberrant tight junctional morphology.…”
Section: Bbb Deficit Subtypes In Psychosissupporting
confidence: 89%
“…Conversely, transcriptomic and genetic studies indicate the presence of disruptions in paracellular 6 and transcellular [7][8][9][10][11][12][13] mechanisms related to BMEC function. There is also increasing evidence for increased BBB permeability in subgroups of patients with SZ 7,14,15 and BD 16,17 . These findings suggest BMEC involvement in the pathogenesis of SZ and BD in specific subgroups of patients, but there is no study to date that has directly investigated the role of BMECs in SZ and BD.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous studies have found the functional relevance of gut microbiome and CRP with the development of anxiety and depression (30,31), the biological mechanism underlying the effects of interaction between gut microbiome and CRP on the risks of anxiety and depression remains to be elucidated (32). In this study, we explored the interaction between CRP and 114 gut microbiome-related traits and observed a signi cant interaction between them for depression and anxiety.…”
Section: Discussionmentioning
confidence: 91%